Investigating the Determinants of NFT Purchase Intention: An Integrated Model Combining the Theory of Planned Behavior and Technology Acceptance Model - Thosporn Sangsawang (Journal of Current Research in Blockchain, 2024)
This study investigated the determinants of Non-Fungible Token (NFT) purchase intention (PI) by integrating the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). The research aimed to identify key factors influencing PI), including Attitude Toward NFTs (AT), Perceived Usefulness (PU), Perceived Ease of Use (PEU), Subjective Norms (SN), Perceived Behavioral Control (PBC), and Perceived Risk (PR). A quantitative research design was employed, with data collected through an online survey distributed via Google Forms in February 2024. Out of the 345 questionnaires initially distributed, 336 were validated and included in the analysis after filtering for participants with actual NFT usage experience. The findings revealed that PU and PEU positively influenced AT, which in turn significantly enhanced PI. PBC and SN were also found to have direct positive effects on PI, highlighting the importance of consumer confidence and social influence in driving behavior. Conversely, PR demonstrated a negative impact on PI, underscoring the deterrent effects of concerns related to security, privacy, and financial uncertainty. The study further confirmed the mediating role of attitude, showing that positive evaluations of NFTs play a crucial role in translating perceived benefits and usability into actionable PI. The integrated model combining TPB and TAM effectively explained the complexities of NFT PI, offering valuable insights for both theoretical understanding and practical applications in the NFT market. These results provide actionable recommendations for NFT platforms and marketers to enhance user engagement, mitigate PR, and foster positive consumer AT.